Perbandingan Perspektif Hukum Pencegahan Kejahatan Dunia Maya dalam Hukum Positif dan Hukum Pidana Islam - Zulfahmi, Zulfahmi; Aulia, Putra; Muklis, Maulana; Pulungan, Rosdewi (Jurnal El-Thawalib, 2025)
This research aims to identify the limitations of Indonesia’s positive legal regulations in addressing cybercrimes and explore the potential integration of relevant Islamic criminal law principles to enhance law enforcement effectiveness. This research employs a normative legal approach by analyzing legislation, legal doctrines, and relevant literature. Cybercrimes, such as hacking, phishing, malware attacks, and cyberbullying, have severe material, psychological, and social impacts, affecting individuals, businesses, and national security. Indonesia’s positive legal framework, particularly the Electronic Information and Transactions (ITE) Law, prescribes penalties of up to 10 years in prison or fines reaching IDR 10 billion. However, enforcement is often hampered by challenges in proving digital evidence, the anonymity of perpetrators, and jurisdictional limitations. From the perspective of Islamic criminal law, cybercrimes are classified as ta’zir offenses, granting judges the flexibility to determine appropriate punishments based on the severity of the crime. Beyond punitive measures, Islamic law emphasizes restorative justice through sincere repentance (taubat nasuha), ethical awareness, and moral guidance to rehabilitate offenders and prevent recidivism. This study underscores the need for a more integrative approach that combines positive legal mechanisms with Islamic ethical principles. Strengthening cooperation between law enforcement, government institutions, and society is crucial to enhancing cybercrime prevention. By integrating positive law with Islamic criminal law principles, this research proposes a comprehensive strategy to address digital crimes more effectively in Indonesia.